2012
DOI: 10.1108/09565691211268162
|View full text |Cite
|
Sign up to set email alerts
|

Archivists 2.0: redefining the archivist's profession in the digital age

Abstract: PurposePublic organizations are investing in e‐government development and e‐services to improve the interaction and services to the citizens. Archivists need to act more pro‐active to capture and manage records in order to be accessible both in the present and in the long‐term. Archivists need to understand the conceptual context and business processes in which the records are created. This study aims to focus on an ongoing process within a specific context, which may have direct, but also future implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
15
0
3
Order By: Relevance
“…Based on the results of the validation, it can be concluded that some of the advantages of e-SiAdes, including the recording of incoming and outgoing mail archives not using books (Fenwick & Brownstone, 2003), Archive serial number entry automatically (Habiburrahman, 2016), Archive search using five archiving systems (Walker, 1996), There are features for uploading and downloading archive files (Kallberg, 2012), Archive reports are already available in the application (Latif & Pratama, 2015), Village electronic administration system is offline (Rifauddin, 2016), increase effectiveness and speed in managing records (Firmansyah, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the validation, it can be concluded that some of the advantages of e-SiAdes, including the recording of incoming and outgoing mail archives not using books (Fenwick & Brownstone, 2003), Archive serial number entry automatically (Habiburrahman, 2016), Archive search using five archiving systems (Walker, 1996), There are features for uploading and downloading archive files (Kallberg, 2012), Archive reports are already available in the application (Latif & Pratama, 2015), Village electronic administration system is offline (Rifauddin, 2016), increase effectiveness and speed in managing records (Firmansyah, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…suatu institusi yang disebabkan tuntutan untuk beradaptasi dengan lingkungan maupun memenuhi kepatuhan pada kebijakan (Harries, 2009, p. 18). Kemunculan informasi elektronik memungkinkan penggunaan informasi dalam banyak tujuan yang berbeda yang sebelumnya belum pernah mampu dicapai (Kallberg, 2012). Sehingga, institusi lebih banyak menciptakan maupun saling berbagi informasi, tak terkecuali arsip dalam format elektronik.…”
Section: Intisariunclassified
“…As stated earlier, the influence of ICTs on the identities of librarians and information professionals is not well understood or studied. Kallberg () examined the attitudes of archivists towards their professional positions and practices with the advent of increased electronic information. Her findings primarily focused on the skills archivists will require to manage both print and electronic records in the future.…”
Section: Identity Information Technologies and Librariansmentioning
confidence: 99%